Uncovering bacterial leaf blight-resistant genes of rice in some advanced lines through molecular marker analysis and pathogenicity assessment - Mohammad M. Haque; Md. Mostofa Faysal; Muhammed A. Hossain; Md. Shahidul H. Bir; Chong, Khim Phin; Md Arshad Ali (German Multidisciplinary Publishing Center (GMPC), 2025)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo) is a longstanding and devastating disease in Bangladesh. Despite its prevalence, only one BLB-resistant rice variety has been developed. To address this, we evaluated 40 advanced rice lines to assess their resistance to a highly virulent Xoo strain. We also aimed to identify potential resistant genes linked to this resistance using five sequence-tagged site (STS) markers corresponding to the f4, Xa5, Xa13, Xa21, and Xa23 genes. The pathogenicity tests revealed that one germplasm was highly resistant, five were resistant, ten were moderately resistant, one was moderately susceptible, twelve were susceptible, and eleven were highly susceptible. In the subsequent molecular analysis, we found that 27 germplasms carried the Xa4 gene, 18 carried the Xa5 gene, and only one carried the Xa13 gene. A wide range of gene combinations was observed among the germplasms, with one germplasm carrying three genes and 15 germplasms carrying two genes in various combinations. The highly resistant BLB-P-003 germplasm was found to have a combination of the Xa4, Xa5, and Xa13 genes, making it the most effective against the Xoo strain. The results of this study contribute to the diversification and enrichment of the rice gene pool, highlighting promising candidates for developing durable BLB-resistant rice varieties in Bangladesh. Additionally, using the area under the disease progress curve (AUDPC) method, we observed a rapid progression of BLB disease in the studied germplasms, underscoring the importance of implementing control measures as soon as symptoms appear in the field.